Impact of primary diagnosis on survival after heart transplant in female recipients of childbearing age: an analysis of the International Society for Heart and Lung Transplantation (ISHLT) Registry. (3rd October 2022) - Macera, F; Cherikh, W S; De Filippis, E M; Ross, H; Stehlik, J; Bhagra, C J
Abstract: Background: Women undergoing heart transplantation (HT) for peripartum cardiomyopathy (PPCM) have been reported to have inferior post-transplant survival. Specific data on the impact of pre-transplant diagnosis on survival in female HT recipients of childbearing age are lacking, but important for pre-conception counseling of women considering a pregnancy. Methods: Retrospective data analysis was conducted using the ISHLT Registry. The primary aim was to study the impact of pre-transplant diagnosis and alloimmunisation on post-transplant survival in women aged 15–45 yrs at time of HT. Secondary outcomes included the impact of primary diagnosis on conditional survival at 5, 10 and 15-yrs post HT. Results: Of 121, 501 HT recipients (Jan 1992–June 2018), 30, 179 (24.8%) were women. 9, 229 (7.6%) were 15–45 yrs at time of HT. Peripartum cardiomyopathy (PPCM) and congenital heart diseases (CHD) was the primary diagnosis in 8.9% and 9.3%, respectively. Overall median post-transplant survival was 15.2 yrs. Female with PPCM were associated with higher alloimmunisation (Figure 1). PPCM was associated with lower survival (median survival in PPCM vs CHD vs other: 9.1 years vs 15.2 years vs 15.5 years respectively, p<0.05). This was not entirely explained by higher alloimmunisation in this group (Figure 2A). Five-year conditional survival of recipients of childbearing age was significantly affected by primary diagnosis of PPCM, and by pediatric status at HT, defined as age <18-yrs (PPCM vs other diagnosis p<0.05; pediatric vs non-pediatric p 0.003), whilst 10- and 15-year conditional survival was not. The difference in 5-year conditional outcome between PPCM and other diagnosis, was not significant however when female recipients were grouped according to their level of alloimmunisation (Figure 2B). Conclusion: PPCM as the primary indication for HT is associated with a worse post HT survival. Our data suggest that this is not entirely explained by alloimmunisation. The impact of previous PPCM appears to be greatest in the first 5 yrs post HT. Further research is needed to fully elucidate the mechanisms associated with worse survival in this group and help inform pre-conception counseling in those HT recipients considering a subsequent pregnancy. Funding Acknowledgement: Type of funding sources: None.